Health Profile Of Aged Persons In Urban & Rural Field Practice Areas Of Medical College, Amrisar - Padda A.S; Mohan V; Singh Jagjit; Deepti S.S; Singh Gurmeet; Dhillon H.S (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the health status of aged persons in urban and rural area? Objectives: 1. To study the socio-demographic profile. 2. To study the health status of aged persons in urban and rural areas and factors associated with it. Study design: Cross-sectional Participants: Persons aged 60 years and above. Sample size: 698 (423 males and 275 females) Study variables: Age, Sex, marital status, occupation, literacy status, addition, morbidity pattern and disability. Results: Among 698 aged persons, 423(60.60%) were males and 275(39.40%) were females, 393(56.3%) were in the age group of 60-65 years while only 34(4.8%) were more than 80 years. Majority (58.45%) belonged to Sikh community followed by Hindus (39.9%). 61.37% aged persons were literate and 38.63% were illiterate. 73.74% of all aged were living in joint families. 68.39% aged persons were engaged in one or other works while 31.61% were dependent on other family members. It was observed that 46.08% of rural aged and 32.97% of urban aged persons were going for morning/evening walk. 33.69% of urban aged and 20.69% of rural aged were reading newspapers or books. Out of total 423 males, 363(85.81%) were addicted to one or the other intoxicants. 374(53.58%) were feeling satisfactory at this age while 324(46.42%) were not feeling so. Majority of them were ill at the time of survey. Arthritis (60.60%) being the commonest cause of illness followed by cataract or visual impairment (54.01%). 16.62% of the aged were hypertensive, it was more (19.35%) in urban aged as compared to rural aged (13.79%). Diabetes mellitus was observed in 5.3% aged persons and it was more commonly seen in urban area (6.81%) than in rural area (2.51%). Prevalence of peptic ulcers/chromic gastritis was found to be 5.87% (6.09% in urban area (6.27%) in rural area aged). The problems due to socio-psychology causes were minimal, probably because majority (73.74%) of them were residing with their families